Who benefits when parents administer intravenous antibiotics, at home, to children with cystic fibrosis? A critical review. - Walsh, Daniel (2009)
Introduction: Cystic fibrosis (C.F.) is the most prevalent hereditary life-limiting disorder in the United Kingdom (Cystic Fibrosis Trust, 2008). Contemporary social policy states that, whenever possible, young people are best cared for at home(Department of Health, 2003; Department of Health, 2004c). Parents are being taught to perform many complex tasks that would only have been undertaken by healthcare professionals, in the hospital setting, in the past. Since the introduction of home intravenous antibiotic therapy, by parents (H.I.V.A.T.) the prevalence of parents administering it has greatly increased.